Public Sector Synergy for Poverty Alleviation (Institutional Collaboration in Blitar Local Government) - Saleh, Choirul; Mustofa, Mochammad Zainal (Universitas Padjadjaran, 2025)
Poverty alleviation is a multidimensional challenge that requires an integrated response at the local government level. This study analyzes institutional collaboration practices in poverty reduction in Blitar Regency, Indonesia, using a qualitative case study approach through interviews, observation, and document analysis. The findings reveal the presence of both formal mechanisms (TKPK forums, planning synchronization, and integrated databases) and operational arrangements (SLRT, Sidaksos, and cross-agency technical teams) that facilitate inter-sectoral coordination. However, persistent challenges remain, including data discrepancies, sectoral ego, limited resources, and low community participation. In response, the local government has introduced institutional innovations such as the Annual Action Plan (RAT), poverty dashboard, Sidaksos application, the Gotong Royong movement, and pentahelix collaborations with universities and the private sector. These findings indicate that collaborative governance, supported by adaptive innovations, can strengthen institutional synergy. The study contributes to the theoretical discourse on network governance and inter-organizational collaboration, while also offering practical insights for enhancing decentralized governance.